Business Model for Effectiveness of Human-AI Collaboration Patterns in Digital Fiction Storytelling: A Systematic Literature Review - Thamrin, Daffa Shidqi (SITEKNIK: Sistem Informasi, Teknik dan Teknologi Terapan, 2025)
The unavoidable pace of Artificial Intelligence (AI) is changing its role from a simple tool to a potential thought partner in various creative fields, including digital storytelling. This research discusses the effectiveness of human-AI collaboration patterns specifically in the aspect of fictional storytelling, for which creativity, narrative structure, and imagination are crucial. By a Systematic Literature Review (SLR), this research synthesizes results from published article research from 2020 to 2025, with the focus on how AI supports and co-creates with human authors throughout the storytelling process. This research also discovered and identified several benefits, which include increased creativity, idea generation, and efficiency, and also discussed challenges such as authority for storytelling, author originality, and ethical considerations in the ownership of a story. This research also discusses implications for future development and proposes a collaboration model that involves two types of human actors, which are writers and editors, and then collaborating with an AI system by a human-centered business design approach. Those results offer a framework business model for implementing practical storytelling systems by results of literature review and suggest that fictional storytelling may be an ideal and potential field for learning about AI's creative potential. The contribution of this research is the aspect of human-centered AI and provides guidelines for designing collaborative storytelling platforms that include both human and AI roles